2022
DOI: 10.3390/ani12030249
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Genetic Diversity in the Endangered “Berrenda” Spanish Cattle Breeds Using Pedigree Data

Abstract: Pedigree analyses of two endangered cattle breeds were performed in order to study the structure and the genetic variability in their populations. Pedigree data were analyzed from 12,057 individuals belonging to the “Berrenda en Negro” cattle breed (BN) and 20,389 individuals belonging to the “Berrenda en Colorado” cattle breed (BC) that were born between 1983 and 2020. BN and BC reference populations (RP) were set up by 2300 and 3988 animals, respectively. The generation interval in BN and BC reference popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
0
10
2
Order By: Relevance
“…These results were influenced by a long history of recording LB animals and by a relatively short period of LZ registration as a breed. In a study focused on endangered Spanish breeds, a lower pedigree completeness level of 82.76% was observed in 'Berrenda en Negro' and 79.57% in 'Berrenda en Colorado' [41]. According to Addo et al [42], the estimated pedigree completeness showed that within the local German breeds, the Angler pedigree was approximately 90.0% complete, which was higher than that of the Red-and-White dualpurpose cattle in the first parental generation.…”
Section: Discussionmentioning
confidence: 97%
“…These results were influenced by a long history of recording LB animals and by a relatively short period of LZ registration as a breed. In a study focused on endangered Spanish breeds, a lower pedigree completeness level of 82.76% was observed in 'Berrenda en Negro' and 79.57% in 'Berrenda en Colorado' [41]. According to Addo et al [42], the estimated pedigree completeness showed that within the local German breeds, the Angler pedigree was approximately 90.0% complete, which was higher than that of the Red-and-White dualpurpose cattle in the first parental generation.…”
Section: Discussionmentioning
confidence: 97%
“…The availability of genomic data has facilitated landscape genomics and conservation studies to accurately estimate genetic diversity and inbreeding [ 8 , 21 , 22 ]. Genomic data enable the accurate assessment of a population structure based on the actual versus expected genetic diversity [ 23 ]. Genomic information, on the other hand, is still limited by the cost of marker genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the number of breeding animals registered in the herd books, BN and BC have a total of 3509 (3.061 females, 448 males and 73 herds) and 6414 (5.390 females, 1.024 males and 140 herds) registrations, respectively, with most of them geographically located in the southern part of the Iberian Peninsula [ 2 ]. The effective population sizes calculated from pedigree data are 12.44 (BN) and 16.62 (BC), respectively [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For more than 20 years, the Berrenda en Negro and Colorado Breeders Association [ 16 ] has been developing corresponding breeding programs in both breeds, including the compilation of pedigree records and the detection of chromosomal alterations in animals that are candidates for breeding. This is aimed at improving the low reproductive performance in the two breeds [ 3 , 17 ], which restrains their conservation potential. Candidates for breeding stock are genetically tested to eliminate rob (1;29) carriers.…”
Section: Introductionmentioning
confidence: 99%